Futebóis em movimento: sexualidades, subjetividades e tensionamentos no circuito esportivo da Champions Ligay - Camargo, Wagner Xavier de (2024)
The research unfolded through ethnographies at Champions LiGay, an event that promotes a circuit of sports competitions based on society football played by gay, bisexual, and transgender males. Observations, interactions, and interviews were conducted with amateur players in the Champions LiGay over six years (2018 to 2023), aiming to construct a long-term ethnography. Over this period, the institutionalization of “gay football” and its transformation into “LGBT football” were observed, accompanied by many controversies in this process. As a guiding thread, this study identified tensions among subjects regarding the themes of amateurism vs professionalism, homosexuality vs heterosexuality, and inclusion vs exclusion. Through this realization, it was observed that the notion of “multiple futebóis” is related to an apparent “peaceful coexistence” of sexual and gender diversity in an ostensibly “alternative” football context. Therefore, the empirical analysis of current actions and representations of amateur players served as a starting point to reflect on gender dissonances in this established scenario. The concept of fractals was borrowed to propose a conceptual resizing of the category “multiple futebóis”. In the end, it is concluded that professionalism prevails as a guiding element in sports practices, heterosexuality operates as a “gay prosthesis”, and the proclaimed “inclusion” is merely tolerated coexistence among groups. The research also puts into perspective the idea of political purpose, questioning the future of these ‘futebóis’.